Pengaruh Motivasi Kerja dan Kompensasi terhadap Kinerja Pegawai di PD BPR Bahterahmas Konawe - Willyam Lakebo; Nasrullah Dalli; Muh. Nur (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research aims to measure work motivation and compensation in measuring employee performance. This research uses quantitative methods. A quantitative approach is a research approach that primarily uses a postpositivist paradigm in developing science (such as thinking about cause and effect, reduction to variables, hypotheses, specific questions, using measurements and observations, and testing theories) using research strategies such as experiments and surveys that require data statistics. The results of this research are 1) Work motivation has a positive and significant effect on employee performance. This shows that the existence of enthusiasm and passion in working to obtain achievement, power and affiliation with fellow employees encourages employees to carry out their duties well so that their performance improves. 2) Compensation has a positive and significant effect on employee performance. This shows that providing compensation in accordance with the output produced by employees results in maximizing employee performance.